A rare case of painful fibroma arising from tendon sheath of flexor hallucis longus - Faris Indra Prahasta, Didi Indra; Bajuri, M. Y.; Rosli, N. (Journal of Krishna Institute of Medical Sciences University (JKIMSU, 2022)
Fibroma of the Tendon Sheath (FTS) is a rare soft tissue tumor commonly found in upper extremities. Usually, the lesions occur in wrists and hands. There are only a few cases of fibroma of the tendon sheath arising from the lower extremities have been reported. This case report describes a rare presentation of painful FTS that arises from flexor hallucis longus at the plantar aspect of the forefoot in a middle age lady. To our knowledge there is only one similar case reported previously.